Biblejskie obrazy v apokrifičeskoj literature (na primere apokrifa „Hoždenie Agapiâ v raj”) - Vorobʹeva, Svetlana N.; Selezneva, Larisa V. (Stylistyka, 2020)
The authors analyze the biblical images that are used in the Apocrypha The Journey of Agapius to Paradise. Apocrypha is a genre that is, as it were, on the periphery of religious discourse. This is due to the fact that they do not perform the actual liturgical functions, and, despite their religious content, belong to non-canonical works that the Church does not recognize as Sacred. Therefore, the Apocrypha is not included in the register and is not considered a rule of faith and piety for believers, like the texts of the Old and New Testaments. The authors use an allegorical way of interpreting the text. It allows revealing the symbolic meaning of the biblical images in the Apocrypha. Biblical images are an important component of religious discourse. Religious values, values of faith are transmitted through them in a direct or veiled form. The main idea of the gospel transmitted through the imagery and specific language-understanding life’s journey as the path to the Kingdom of heaven, which lies over either the monastery or through the desert, through many feats of restraint of the flesh. This formed the idea of asceticism as a form of rejection of earthly reality with its orders, temptations and delusions. The architectonics of the work is formed by the chronotope of the road. On the road the paths of different characters cross. The motive of the meeting plays a leading role in religious discourse. The Apocrypha The Journey of Agapius to Paradise is based on the seven meetings of Agapius, which are the organizational centers of the main events. The motive of the meeting intersects with the motive of the Epiphany in different guises: during the journey Agapius encounters on his way an eagle, a child, 12 Apostles, the Lord, prophet Elijah. Due to these images, the metaphorization of the way-road is filled with a new meaning (“the road to God”, “the road to Paradise”, “the path of spiritual transformation”) and its chronotopic value is expanded.